DIVERSITY AND ABUNDANCE OF SOIL-BORNE PATHOGENIC FUNGI IN VARIOUS LAND-USE SYSTEMS IN SUMBERJAYA, LAMPUNG - Joko Prasetyo; Titik Nur Aeny . (Universitas Lampung, 2006)
Diversity and abundance of soil-borne pathogenic fungi in various land-use systems in Sumberjaya, Lampung. This study was aimed to investigate the effects of land use systems on diversity and abundance of soil-borne pathogenic fungi. Soil samples were collected from Sumberjaya area, West-Lampung, during October 2004. A total of 88 soil samples were collected from seven land use systems: (1) undisturbed forest, (2) disturbed forest, (3) shrub, (4) polyculture coffee, (5) monoculture coffee, (6) food crop, and (7) horticulture crop. The soil samples were laboratory analyzed to isolate and enumerate viable fungal propagules using bioassay procedure by a modified most probable number technique. The results of the study showed that land-use systems had different impacts on diversity and abundance of soil-borne pathogenic fungi. The diversity declined in non-agricultural systems from undisturbed forest to disturbed forest, shrub, and polyculture coffee, and then increased in agricultural systems from polyculture coffee to monoculture coffee, and food crop. In horticulture crop, however, the diversity was lower than that of in food crop system. The abundance had a similar trend except for horticulture crop that showed the highest population. The occurrence of soil-borne pathogens was different across land use systems. Fusarium spp. dominated all land uses, except in shrub that was dominated by Curvularia spp. Botryodiplodia spp. occurred in undisturbed and disturbed forests, decreased in shrub and then disappeared in other land uses. The occurrence of Phytophthora spp. and Pythium spp. was limited in undisturbed and disturbed forest, then disappeared in shrub, in polyculture and monoculture coffee, but increased significantly in food crops. Rhizoctonia sp. only occurred in undisturbed forest.